A contribuição da interação social por meio de jogos na aprendizagem de matemática - Pereira, Susy Stella Dias (2025)
This study investigates the contribution of social interaction in the learning of mathematics through educational games, with 7th grade elementary school students. Admittedly, some challenges are common in the teaching of mathematics, such as demotivation, anxiety and conceptual difficulties. This research is justified by the need to explore methodologies such as educational games, which use social interaction to overcome challenges in the teaching of mathematics. And, in view of this scenario, the question is: How does social interaction among 7th grade elementary school students, mediated by educational games, contribute to the learning of mathematics? The general objective is to develop an investigative process based on experience on the contribution of social interaction in the learning of mathematics, through the application of the Educational Product, specifically through the board game as an activity. As a theoretical basis, three main authors were used as references: Lev Semyonovich Vygotsky with the historical-cultural theory, which emphasizes the role of social interaction and the mediation of culture in the learning process; Alexei Leontiev with the Activity Theory, which points out the importance of practical activity and the social context in human development. And Daniil Borisovich Elkonin and his research on children's games as a central activity for children's cognitive and social development. Also worthy of note is the contribution of the Problem Solving approach, by George Polya. The research was developed at Colégio Estadual Otaviano de Moraes, involving students who actively participated in the proposed activities. The methodology adopted is qualitative in nature, from the perspective of action research, and uses participant observation and document analysis as instruments. As an Educational Product, an E-book with proposals for educational games and collaborative teaching strategies is presented. With categories arising from Activity Theory, the Zone of Proximal Development and Play, the meetings with the students were analyzed. As a result, it was understood that social interaction, mediated by educational games, acted as a catalyst for the students' comprehensive development. An improvement in mathematical skills stands out, but also the development of socio-emotional skills that make it possible to overcome matophobia and transform the learning environment into a space for the collective construction of knowledge and personal development. The educational product that accompanies this dissertation is available on the Educapes platform http://educapes.capes.gov.br/handle/capes/1174129.